ANALISIS PENERAPAN PUBLIC FINANCE MANAGEMENT DI KABUPATEN KEEROM PROVINSI PAPUA - Charley M. Bisai; Anthonius H. Citra Wijaya (Jurnal Kajian Ekonomi dan Studi Pembangunan, 2014)
This study aims to obtain a clear image as well as evaluate the extent of local government and the regions have implemented the Public Finance Management, (PFM) efficiently and effectively and in accordance with applicable legislation. Assessment of financial management areas include some aspects: (1) framework of legislation; (2) planning and budgeting; (3) management of cash; (4) the procurement of goods and services; (5) accounting and reporting; (6) internal control; (7) debt and public investment; (8) management of assets; and (9) auditing and external oversight. Research data was collected using a survey method; questionnaires and in-depth interviews with respondent in the Local Government of Keerom, one of the districts in the Papua Province which is directly adjacent to the country of Papua New Guinea. PFM data were analyzed and interpreted using descriptive analysis techniques. The results of the study showed that financial management in Keerom less than the maximum. From the nine aspects of assessment only the procurement of goods and services that achieved a score of 55 percent, while the other eight aspects ranging between 44-20 percent by placing audit and external oversight at the very last position with a score of 20 percent. This study recommends that each regional work unit (SKPD) to recruit employees by prioritizing the needs of employees in the accounting field for each SKPD with the purpose of assisting the implementation of accounting so that SKPD can make the financial report in accordance with applicable regulations. In addition, it is expected that Keerom makes Regulation on the main points of sectoral asset management and regulation of the regional head guidelines for the administration of property area.Keywords:Public Finance Management, Accounting